Character Strengthening Training for Unggul Cut Nyak Dhien High School Using Managerial Training Methods: Pelatihan Penguatan Karakter Guru SMA Unggul Cut NYak Dhien Langsa Dengan Metode Diklat Managerial - Husaini; Weni Astari; Fahrul Reza (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
To get quality students as a result of quality education, quality teachers are also needed. One of the benchmarks of quality education is good student character. This can be achieved by presenting teachers who understand character education. The purpose of this community service activity is to improve the ability of teachers to foster teacher character by using managerial model training. This activity uses a qualitative descriptive method with a training model in the form of training and mentoring for teachers. The subjects of this PKM program are 5 homeroom teachers at SMA Unggul Cut Nyak Dhien. The results of the community service implementation show an increase in the understanding and ability of training participants towards character education.